The Development of Malay Dessert Module : Bubur and Pengat - Abdul Rahman, Abdul Wafi; Md Sahak, Adibah Aishah; Yusri, Nabilah; Raden Ismail, Raden Mohd Farhan Helmy; Rohiat, Mohd Akmal (Research and Innovation in Technical and Vocational Education and Training, 2021)
Malaysia is one of the few places where one could find  an amalgamation of flavours and varieties of heritage food,  which  stands  a  living  proof  of  the   famous motto Malaysia, Truly Asia. The availability of local resources in this country allows the creation of flavourful, delicious, unique, and authentic recipes. In this modern era, many have forgotten the uniqueness of cooking techniques and practices in Malay cuisine that our ancestors have passed on to us. Although modernization takes place in the foodways, the values associated with other Malay customs that have been practiced by the family and the rest of the Malay community remain until today. There are many types of traditional food in Malaysia, such as dishes and desserts. There are many varieties of desserts that can be found in all states of Malaysia. in the modern days, Malay desserts can be eaten at any time of the day,  as  light  breakfast, afternoon snack, or dessert. The development of module Malay Dessert in “Bubur and Pengat is an alternative  for users to find and learn Malay dessert in Bubur and Pengat easily.The objectives of the research were to develop Malay dessert modulein Bubur and Pengat especially for all who have take the Culinary Art course and access the utility of a module Malay dessert  in“Bubur and Pengat” that consists of content, format, clarity and module presentation design. The development of the module were used ADDIE model that consist of  five elements to develop the module. The process of making this module is using Microsoft word, p and Canva. This module has been developed and produced based on a few key topics. Analyzes of data from experts who validate reviews suggest that these modules work well and have appropriate content on the basis of pastry. As a result of the development of this module, users will be able to easily understand the topics of Malay dessert  in “Bubur and Pengat and being the attractiveness of Malay traditional desserts.